Breast cancer epidemiology and sociodemographic differences in BRICS-plus countries from 1990 to 2019: An age period cohort analysis - Sumaira Mubarik; Fang Wang; Adeel Ahmad Nadeem; Muhammad Fawad; Chuanhua Yu (Elsevier, 2023)
Background: Breast cancer (BC) is a major health concern in the BRICS-plus, a group of developing nations consisting of Brazil, Russia, India, China, South Africa, and 30 other Asian countries, with nearly half of the world's population. This study aims to identify potential risk factors contributing to the burden of BC by assessing its epidemiological and socio-demographic changes. Methods: Data on BC outcomes were obtained from the 2019 Global Burden of Disease Survey. The age-period-cohort (APC) modeling technique was used to evaluate the nonlinear impacts of age, cohort, and period on BC outcomes and reported risk attributable mortality and disability adjusted life years (DALYs) rate changes between 1990 and 2019. Results: In 2019, there were 0.90 million female BC cases and 0.35 million deaths in the BRICS-plus region, with China and India having the largest proportion of incident cases and deaths, followed by Pakistan. Lesotho experienced the highest annualized rates of change (AROC: 2.61%; 95%UI: 1.99-2.99) in the past three decades. Birth cohorts' impact on BC varies greatly between the BRICS-plus nations, with Pakistan suffering the largest risk increase in the most recent cohort. High body mass index (BMI), high fasting plasma glucose (FPG), and a diet high in red meat contributed to the highest death and DALYs rates in most BRICS-plus nations in 2019, and there was a strong negative link between SDI and death and DALYs rate. Conclusions: The study found that the burden of BC varies significantly between BRICS-plus regions. Thus, BRICS-plus nations should prioritise BC prevention, raise public awareness, and implement screening efficiency measures to reduce the burden of BC in the future, as well as strengthen public health policies and initiatives for important populations based on their characteristics and adaptability.